Rectal artesunate suppositories for the pre-referral treatment of suspected severe malaria. - James A Watson; Thomas J Peto; Nicholas J White (PLoS Medicine)
In this Policy Forum article, James A. Watson and colleagues discuss recent guidelines relating to pre-referral treatment of suspected severe malaria with rectal artesunate suppositories in remote areas.